Gender differences in innovation and competitive settings - Schmallenbach, L. (Universität Mannheim, 2022)
This thesis adds to the growing body of literature at the intersection of economic sociology and psychology on how gender differences shape outcomes via supply- and demand-side factors, by putting the spotlight on women and men top performers in competitive settings. It is particularly important to look at gender differences and their effect on outcomes in these settings for three reasons. First, top performers contribute disproportionately to value creation, economic growth, and innovation (Aguinis and O'Boyle Jr 2014), implying a strong lever for gender differences to materialize. Second, it remains to be understood whether gender differences that have been indicated for the general population also apply to men and women in these specific settings (Adams and Funk 2012). Third, due to the underrepresentation of women in the most competitive segments of the labor market (e.g., AAUW 2015), there is an unmet need for large-scale empirical evidence. In combination with the first two points, this evidence is important to not only understand drivers and antecedents of the prevailing gender gap in competitive settings, but also to highlight the gendered potential in human capital that is likely foregone. This evidence can help to derive and articulate countermeasures aimed at increasing the representation of women in such settings.